Národní identita a běloruští političtí emigranti - Šmídová, Michaela (Lidé města, 2006)
This contribution is concerned with the ethnic identity of Byelorussian political emigrants, i. e. very small and narrowly focused group of people living in the Czech Republic and composed of either asylum seekers or asylum recipients. It is an attempt to analyze their testimonies regarding whole range of connections, associations and contents of what it means to be Byelorussian. Everybody has his own view of national or ethnic identity which he demonstrates, declares or experiences somewhat differently. This psychological or personal interdependence is fundamental to experience national identity, the fact also demonstrated in these interviews. These very interviews testify about a great diversit how Byelorussians self-identity, what expressions they use, and how they express their emotional interests.